Surface modified low-pass hemodialysis membrane as well as preparation method and application thereof

By forming a two-dimensional network structure of aminobenzene and sulfonic acid aldehydes on the inner surface of the low-flux hemodialysis membrane, the problems of small pore size and poor biocompatibility of the low-flux hemodialysis membrane are solved, achieving efficient toxin removal and stable dialysis effect.

CN121314408APending Publication Date: 2026-01-13CHONGQING TIANWAITIAN BIOTECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511496431.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing low-flux hemodialysis membranes suffer from problems such as small pore size, low membrane porosity, and poor biocompatibility, resulting in insufficient toxin removal capacity. Furthermore, partial blockage of the membrane pores can actually reduce the toxin removal capacity of the dialysis membrane.

Method used

Using polyethersulfone hollow fiber membrane as the base membrane, a two-dimensional network structure is formed on the inner surface of the membrane by aminobenzene substances and sulfonic acid-containing aldehydes, generating a modified coating with an average pore size of about 1.5 nm, which enhances the membrane's toxin removal ability and improves biocompatibility.

Benefits of technology

It improves the porosity and biocompatibility of low-flux hemodialysis membranes, enhances toxin removal efficiency, especially the removal of medium-molecular-weight toxins, reduces the albumin screening coefficient, and provides more stable and efficient dialysis support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a surface-modified low-pass hemodialysis membrane as well as a preparation method and application thereof, and belongs to the technical field of hemodialysis membranes. The dialysis membrane comprises a base membrane and a modified coating located on the inner surface of the base membrane. The base membrane is a polyether sulfone hollow fiber membrane; the modified coating is of a two-dimensional net structure formed by an aminobenzene substance and an aldehyde substance containing a sulfonic acid group through a polymerization reaction, and the average pore diameter of the structure is 1.5-1.8 nm. Furthermore, the invention also provides a preparation method of the surface-modified low-pass hemodialysis membrane and application of the surface-modified low-pass hemodialysis membrane in a hemodialyzer. The hemodialysis membrane provided by the invention has the advantages that the hemodialysis membrane has a low ultrafiltration coefficient, so that the hemodialysis membrane still keeps relatively high toxin removal efficiency on the premise of low transmembrane and low ultrafiltration coefficient, and has relatively good biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of hemodialysis membrane preparation, and particularly relates to a surface-modified low-flux hemodialysis membrane and a preparation method and application thereof. BACKGROUND

[0002] Hemodialysis technology is a core treatment means for patients with acute and chronic renal failure to survive, and its basic principle is to replace the lost function of the kidney to remove metabolic waste, excess water and electrolytes in the blood through the selective filtration characteristics of the semi-permeable membrane, and to maintain the body's environmental homeostasis. According to clinical statistics, more than 75% of patients with end-stage renal disease (ESRD) in the world rely on hemodialysis to maintain life, and low-flux hemodialysis devices are still the most widely used dialysis devices in clinical use due to their mature technology and high safety. From the technical composition, the performance core of the dialysis device lies in the membrane material and structural design. Low-flux dialysis membrane generally refers to a membrane type with an ultrafiltration coefficient (Kuf) <10 ml / (h·mmHg), and its pore size range is concentrated in 1-2 nanometers, mainly for efficient removal of small molecular toxins (such as urea and creatinine) with a molecular weight below 500 daltons. Compared with high-flux membranes, low-flux membranes have smaller pore sizes and denser structures, which can effectively prevent the loss of essential proteins such as albumin during treatment, and reduce the risk of endotoxin backflow, thereby providing a safer treatment option for patients with unstable hemodynamics or combined low-proteinemia.

[0003] However, due to the defects of the membrane material itself, low-flux dialysis membranes still have many shortcomings, such as small pore size, low porosity, poor biocompatibility, and low removal capacity for low-molecular-weight toxins. In the face of these shortcomings, patent CN107930416A proposes to fix heparin on the surface of a polylactic acid membrane to form a positive charge barrier in combination with chitosan quaternary ammonium salt, thereby inhibiting bacterial penetration and reducing platelet aggregation. CN113559720A constructs a heparin-like modified coating loaded with carboxyl and sulfonic acid groups on the surface of the hemodialysis membrane through covalent reaction of amino and thiol groups with the ortho-phenylenediamine of polyphenol and the self-polymerization and adhesion of polyphenol. This significantly improves the hydrophilicity, blood compatibility and anti-pollution of the membrane material. CN110756066B discloses a sulfonated citric acid chitosan modified polysulfone hemodialysis membrane and a preparation method thereof. The sulfonated citric acid chitosan modified polysulfone (SCACS-PSF) is used as the membrane material, and a biocompatible sulfonated citric acid chitosan modified polysulfone hemodialysis membrane is prepared by a dry-wet spinning method. The membrane has good anticoagulant and antibacterial properties. The above-mentioned patents all aim to improve the biocompatibility of the membrane and enhance the anticoagulant effect of the membrane by modifying the surface of the membrane, but the toxin removal capacity of the membrane has not been improved, on the contrary, due to the modification of the membrane surface, the membrane pores are partially blocked, and the toxin removal capacity of the dialysis membrane is actually reduced.

[0004] Therefore, it is of great significance to research and develop low-flux hemodialysis membranes with high porosity, high biocompatibility and high toxin clearance capacity. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a surface-modified low-flux hemodialysis membrane and its preparation method. The method first prepares a hollow fiber hemodialysis membrane with a pore size of approximately 3 nm using polyethersulfone resin as a raw material. This membrane is then fabricated into a dialyzer. Finally, the inner surface of the membrane is modified using aminobenzene-based substances and sulfonic acid-containing aldehydes. This modification creates a two-dimensional network structure with highly concentrated pores and an average pore size of approximately 1.5 nm. The structure contains a large number of sulfonic acid groups, which enhances the membrane's toxin removal capacity while significantly improving its biocompatibility, providing gentler, more stable, and more efficient dialysis support for patients with fragile kidney disease.

[0006] To achieve the objectives of this invention, the following technical solution is adopted: First, this invention provides a surface-modified low-flux hemodialysis membrane, the dialysis membrane comprising a base membrane and a modified coating located on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane; the modified coating is a two-dimensional network structure formed by the polymerization reaction of aminobenzene substances and aldehyde substances containing sulfonic acid groups, the average pore size of the structure is 1.5-1.8 nm, and the two-dimensional network structure is rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0007] Preferably, the average pore size of the inner surface of the polyethersulfone hollow fiber membrane is 2.8–3.2 nm; Preferably, the aminobenzene compound is selected from one or more of 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 1,3,5-tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene, 1,3,5-tris(N-(p-tert-butylphenyl)-N-(4-biphenyl)amino)benzene, 1,3,5-triaminobenzene, and 1,3,5-trimethyl-2,4,6-tris[3,5-di(4-aminophenyl)phenyl]benzene.

[0008] Preferably, the sulfonic acid-containing aldehyde is selected from one or more of 2,5-disulfonic terephthalaldehyde, 4,4'-disulfonic biphenyl aldehyde, 2-sulfonic-1,3-propanedialdehyde, and 1,2-bis(sulfonic acid methoxy)glyoxal.

[0009] Preferably, the spinning solution of the base film contains the following components by mass fraction: Polyethersulfone resin: 14%–18%; Pore-forming agent: 1.5%–4.0%; Organic solvent A: 75%–80%; RO water: 1%~3%; The core fluid of the base membrane contains the following components by mass fraction: Organic solvent A: 40%–50%; RO water: 50%~60%; The RO water mentioned above is water purified using reverse osmosis technology.

[0010] Preferably, the organic solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0011] Preferably, the pore-forming agent is one or more of polyvinylpyrrolidone and polyethylene glycol.

[0012] Preferably, the polyethersulfone hollow fiber membrane has an inner diameter of 190–210 μm and a wall thickness of 33–45 μm.

[0013] Secondly, the present invention provides a method for preparing the above-mentioned surface-modified low-flux hemodialysis membrane, characterized by comprising the following steps: (1) Preparation of polyethersulfone hollow fiber membrane: Polyethersulfone resin, pore-forming agent, organic solvent A and RO water are mixed and stirred and degassed to obtain spinning solution; organic solvent A and RO water are mixed to obtain core solution, and spinning is carried out by phase inversion method. After washing and drying, polyethersulfone hollow fiber membrane with an average pore size of 2.8 to 3.2 nm on the inner surface is obtained. (2) Aminobenzene deposition: Circulate organic solvent B containing 0.1-1.0 mol / L aminobenzene substances on the inner surface of the polyethersulfone hollow fiber membrane described in step (1) for 6-10 h, and vacuum dry at 75-85 °C to constant weight; (3) Sulfonic acid aldehyde modification: The aqueous solution of aldehyde containing 0.15-1.5 mol / L sulfonic acid groups is circulated at 75-85°C on the inner surface of the polyethersulfone hollow fiber membrane after step (2) for 4-6 hours, and then vacuum dried at 75-85°C to constant weight.

[0014] Preferably, the cycles described in steps 2 and 3 are performed in a dialyzer.

[0015] Preferably, the stirring in step (1) is carried out at 70-90°C for 5-10 hours; the degassing is carried out under vacuum for 8-12 hours.

[0016] Preferably, the organic solvent B is one or more of methanol, ethanol, and acetonitrile.

[0017] Finally, the present invention provides a hemodialysis device made from a surface-modified low-pass hemodialysis membrane as described above.

[0018] This invention first prepares a high-flux hollow fiber hemodialysis membrane with an average inner surface pore size of about 3 nm using a phase transfer method. Then, it modifies the inner surface of the membrane using aminobenzene-based substances and aldehydes containing sulfonic acid groups, forming a two-dimensional network structure with an average pore size of about 1.5 nm and a thickness of 10–20 nm on the inner surface of the membrane. The resulting technical effects are as follows: (1) Aminobenzene substances and sulfonic acid-containing aldehydes can form a two-dimensional network structure on the membrane surface, which greatly improves the porosity of the hemodialysis membrane, ensuring that it has a low ultrafiltration coefficient, so that it can still maintain a high toxin removal efficiency under the premise of low transmembrane pressure and low ultrafiltration coefficient. (2) A large number of sulfonic acid groups are introduced into the two-dimensional network structure on the inner surface of the membrane. The strong negative charge and hydrogen bonding of sulfonic acid groups make it easy to combine with water molecules, forming a hydration layer on the inner surface of the membrane, optimizing the protein adsorption conformation, regulating cell behavior and inhibiting coagulation / inflammatory response, thus greatly improving the biocompatibility and anticoagulation effect of the membrane. (3) Through characterization tests, the average pore size of the two-dimensional network structure formed on the inner surface of the membrane is about 1.5 nm and the thickness is 10-20 nm. The pore size distribution of the membrane is highly concentrated in 1.5-1.8 nm. Through experiments, the sieving coefficient of albumin is less than 0.01, but the toxin removal efficiency is greatly improved. Compared with traditional low-flux dialysis membranes, the removal efficiency of medium molecular toxins such as β2-microglobulin is also improved. Detailed Implementation

[0019] The present invention will be further described in detail below with reference to embodiments, but this does not limit the present invention in any way. Any modifications or improvements made based on the teachings of the present invention shall fall within the protection scope of the present invention.

[0020] The processes, conditions, reagents, and experimental methods used in implementing this invention, except as specifically mentioned below, are all common knowledge and general knowledge in the field, and this invention does not have any particular limitations. Experimental methods in the embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer.

[0021] The main sources of reagents and consumables in the following examples are: Polyethersulfone (PES): BASF (China) Co., Ltd.; Polyvinylpyrrolidone (PVP): BASF (China) Co., Ltd.; Polyethylene glycol (PEG): Shanghai Aladdin Biochemical Technology Co., Ltd.; N'N-Dimethylformamide (DMF): Shandong Jinkong Riyue New Materials Co., Ltd.; N'N-Dimethylacetamide (DMAc): Shandong Jinkong Riyue New Materials Co., Ltd.; Methanol: Shanghai Maclean Biochemical Technology Co., Ltd.; Ethanol: Shanghai Maclean Biochemical Technology Co., Ltd.; Acetonitrile: Shanghai Maclean Biochemical Technology Co., Ltd.; 1,3,5-Tris(4-aminophenyl)benzene: Shanghai Maclean Biochemical Technology Co., Ltd. Shanghai Maclean Biotech Co., Ltd.; 2,5-Disulfonic terephthalaldehyde; 2,4,6-Tris(4-aminophenyl)-1,3,5-triazine; 1,3,5-Tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene; 1,3,5-Triaminobenzene; 1,3,5-Trimethyl-2,4,6-Tris[3,5-di(4-aminophenyl)phenyl]benzene; 1,3,5-Triaminobenzene; 1,3,5-Trimethyl-2,4,6-Tris[3,5-di(4-aminophenyl)phenyl]benzene; Example 1 A dialysis membrane includes a base membrane and a modified coating on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane with an average pore size of 3 nm on its inner surface; the modified coating is a two-dimensional network structure formed by polymerization of 1,3,5-tris(4-aminophenyl)benzene and 2,5-disulfonic acid-based terephthalaldehyde, with an average pore size of 1.5 nm, and the two-dimensional network structure is rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0022] Its preparation method is as follows: Step (1) Preparation of hollow fiber dialysis membrane: Weigh 18% polyethersulfone resin, 3% PVP, 76% N,N-dimethylformamide, and 3% RO water according to the mass fraction and mix them. Stir at 80℃ for 10h to form a uniform spinning solution. After vacuum degassing for 12h, the core solution is composed of 45% N,N-dimethylformamide and 55% RO water. Then, spin the solution using the phase inversion method, wash and dry it to obtain a polyethersulfone hollow fiber membrane with an inner pore size of about 3nm. Then, the polyethersulfone hollow fiber membrane is used to prepare a hemodialysis machine.

[0023] Step (2) Deposition of aminobenzene-like substances on the inner surface of the membrane: The dialysate inlet and outlet of the hemodialyzer obtained in step (1) are blocked, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 1,3,5-tris(4-aminophenyl)benzene is weighed and dissolved in ethanol to prepare a 0.1 mol / L mixed solution. The prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 8 hours at room temperature. Then the dialyzer is removed and dried in a vacuum drying oven at 80°C for 4 hours to obtain a hemodialyzer with a certain amount of 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane.

[0024] Step (3) Preparation of modified coating: The dialysate inlet and outlet of the hemodialyzer from step (2) are blocked again, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 2,5-disulfonic acid terephthalaldehyde is weighed and dissolved in pure water to prepare a 0.15 mol / L mixed solution. Under the condition of 80℃, the prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 5 hours to react with the 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialyzer is removed and dried and sterilized to obtain the modified low-pass hemodialyzer.

[0025] Example 2 A dialysis membrane includes a base membrane and a modified coating on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane with an average pore size of 2.8 nm on its inner surface; the modified coating is a two-dimensional network structure formed by polymerization of 1,3,5-tris(4-aminophenyl)benzene and 4,4'-disulfonic acid-based biphenyl dicarboxaldehyde, with an average pore size of 1.7 nm, and the two-dimensional network structure is rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0026] Step (1) Preparation of hollow fiber membrane dialyzer: Weigh 14% polyethersulfone resin, 3% polyethylene glycol, 80% N-methylpyrrolidone, and 3% RO water according to the mass fraction and mix them. Stir at 70°C for 10 h to form a homogeneous spinning solution. After vacuum degassing for 12 h, the core solution is composed of 40% N,N-dimethylformamide and 60% RO water. Then, spin the solution using the phase inversion method, wash and dry it to obtain a polyethersulfone hollow fiber membrane with an inner pore size of about 2.8 nm. Then, prepare the polyethersulfone hollow fiber membrane into a hemodialysis machine.

[0027] Step (2) Deposition of aminobenzene-like substances on the inner surface of the membrane: The dialysate inlet and outlet of the hemodialyzer obtained in step (1) are blocked, and the blood inlet and outlet are connected to the peristaltic pump tubing. A certain mass of 1,3,5-tris(4-aminophenyl)benzene is weighed and dissolved in methanol to prepare a 0.2 mol / L mixed solution. The prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 10 h at room temperature. Then the dialyzer is removed and dried in a vacuum drying oven at 85 ℃ for 4 h to obtain a hemodialyzer with a certain amount of 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane.

[0028] Step (3) Preparation of modified coating: The dialysate inlet and outlet of the hemodialyzer from step (2) are blocked again, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 4,4'-disulfonic acid biphenyl dicarboxaldehyde is weighed and dissolved in pure water to prepare a 0.30 mol / L mixed solution. Under the condition of 85℃, the prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 4 hours to react with the 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialyzer is removed and dried and sterilized to obtain the modified low-flux hemodialyzer.

[0029] Example 3 A dialysis membrane includes a base membrane and a modified coating on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane with an average pore size of 3.2 nm on its inner surface; the modified coating is a two-dimensional network structure formed by polymerization of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2,5-disulfonic acid-based terephthalaldehyde, with an average pore size of 1.6 nm, and the two-dimensional network structure is rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0030] Step (1) Preparation of hollow fiber membrane dialyzer: Weigh 16% polyethersulfone resin, 1.5% PVP, 80% dimethyl sulfoxide, and 2.5% RO water according to the mass fraction and mix them. Stir at 90℃ for 5h to form a uniform spinning solution. After vacuum degassing for 8h, the core solution is composed of 50% N,N-dimethylformamide and 50% RO water. Then, spin the solution using the phase inversion method, wash and dry to obtain a polyethersulfone hollow fiber membrane with an inner pore size of about 3.2nm. Then, prepare the polyethersulfone hollow fiber membrane into a hemodialysis device.

[0031] Step (2) Deposition of aminobenzene compounds on the inner surface of the membrane: The dialysate inlet and outlet of the hemodialyzer obtained in step (1) are blocked, and the blood inlet and outlet are connected to the peristaltic pump tubing. A certain mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is weighed and dissolved in acetonitrile to prepare a 0.4 mol / L mixed solution. The prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 6 hours at room temperature. Then the dialyzer is removed and dried in a vacuum drying oven at 80°C for 5 hours to obtain a hemodialyzer with a certain amount of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine deposited on the inner surface of the membrane.

[0032] Step (3) Preparation of modified coating: The dialysate inlet and outlet of the hemodialyzer from step (2) are blocked again, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 2,5-disulfonic acid terephthalaldehyde is weighed and dissolved in pure water to prepare a 0.60 mol / L mixed solution. Under the condition of 75℃, the prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 4 hours to react with the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialyzer is removed and dried and sterilized to obtain the modified low-flux hemodialyzer.

[0033] Example 4 A dialysis membrane includes a base membrane and a modified coating on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane with an average pore size of 3 nm on its inner surface; the modified coating is a two-dimensional network structure formed by polymerization of 1,3,5-tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene and 2,5-disulfonic acid-based terephthalaldehyde, the structure having an average pore size of 1.5 nm and being rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0034] Step (1) Preparation of hollow fiber membrane dialyzer: Weigh 16% polyethersulfone resin, 1.5% PVP, 80% N,N-dimethylformamide, and 2.5% RO water according to the mass fraction and mix them. Stir at 80℃ for 8h to form a homogeneous spinning solution. After vacuum degassing for 10h, the core solution is composed of 50% N,N-dimethylformamide and 50% RO water. Then, spin the solution using the phase inversion method, wash and dry it to obtain a polyethersulfone hollow fiber membrane with an inner pore size of about 3nm. Then, prepare the polyethersulfone hollow fiber membrane into a hemodialysis machine.

[0035] Step (2) Deposition of aminobenzene-like substances on the inner surface of the membrane: The dialysate inlet and outlet of the hemodialyzer obtained in step (1) are blocked, and the blood inlet and outlet are connected to the peristaltic pump tubing. A certain mass of 1,3,5-tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene is weighed and dissolved in ethanol to prepare a 0.6 mol / L mixed solution. The prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 8 hours at room temperature. Then the dialyzer is removed and dried in a vacuum drying oven at 80°C for 4 hours to obtain a hemodialyzer with a certain amount of 1,3,5-tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene deposited on the inner surface of the membrane.

[0036] Step (3) Preparation of modified coating: The dialysate inlet and outlet of the hemodialyzer from step (2) are blocked again, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 2,5-disulfonic acid terephthalaldehyde is weighed and dissolved in pure water to prepare a 0.90 mol / L mixed solution. Under the condition of 80℃, the prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 5 hours to react with the 1,3,5-tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialyzer is removed and dried and sterilized to obtain the modified low-flux hemodialyzer.

[0037] Example 5 A dialysis membrane includes a base membrane and a modified coating on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane with an average pore size of 2.9 nm on its inner surface; the modified coating is a two-dimensional network structure formed by the polymerization reaction of 1,3,5-triaminobenzene and 2,5-disulfonic acid-based terephthalaldehyde, with an average pore size of 1.8 nm, and the two-dimensional network structure is rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0038] Step (1) Preparation of hollow fiber membrane dialyzer: Weigh 16% polyethersulfone resin, 4% PVP, 79% N,N-dimethylformamide, and 1% RO water according to the mass fraction, mix them, stir at 85℃ for 9h to form a homogeneous spinning solution, and after vacuum degassing for 10h, the core solution is composed of 50% N,N-dimethylformamide and 50% RO water. Then, use the phase inversion method to spin, wash, and dry to obtain a polyethersulfone hollow fiber membrane with an inner pore size of about 2.9nm; then prepare the polyethersulfone hollow fiber membrane into a hemodialysis device.

[0039] Step (2) Deposition of aminobenzene-like substances on the inner surface of the membrane: The dialysate inlet and outlet of the hemodialyzer obtained in step (1) are blocked, and the blood inlet and outlet are connected to the peristaltic pump tubing. A certain mass of 1,3,5-triaminobenzene is weighed and dissolved in ethanol to prepare a 0.8 mol / L mixed solution. The prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 8 hours at room temperature. Then the dialyzer is removed and dried in a vacuum drying oven at 80℃ for 4 hours to obtain a hemodialyzer with a certain amount of 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane.

[0040] Step (3) Preparation of modified coating: The dialysate inlet and outlet of the hemodialyzer from step (2) are blocked again, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 2,5-disulfonic acid terephthalaldehyde is weighed and dissolved in pure water to prepare a 1.2 mol / L mixed solution. Under the condition of 80℃, the prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 5 hours to react with the 1,3,5-triaminobenzene deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialyzer is removed and dried and sterilized to obtain the modified low-flux hemodialyzer.

[0041] Example 6 A dialysis membrane includes a base membrane and a modified coating on the inner surface of the base membrane; the base membrane is a polyethersulfone hollow fiber membrane with an average pore size of 3.1 nm on its inner surface; the modified coating is a two-dimensional network structure formed by the polymerization reaction of 1,3,5-trimethyl-2,4,6-tris[3,5-di(4-aminophenyl)phenyl]benzene and 2,5-disulfonic acid terephthalaldehyde, the structure having an average pore size of 1.6 nm and being rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.01.

[0042] Step (1) Preparation of hollow fiber membrane dialyzer: Weigh 16% polyethersulfone resin, 4% PVP, 75% N,N-dimethylformamide, and 3% RO water according to the mass fraction and mix them. Stir at 90℃ for 50h to form a homogeneous spinning solution. After vacuum degassing for 12h, the core solution is composed of 45% N,N-dimethylformamide and 65% RO water. Then, spin the solution using the phase inversion method, wash and dry it to obtain a polyethersulfone hollow fiber membrane with an inner pore size of about 3.1nm. Then, prepare the polyethersulfone hollow fiber membrane into a hemodialysis device.

[0043] Step (2) Deposition of aminobenzene-like substances on the inner surface of the membrane: The dialysate inlet and outlet of the hemodialyzer obtained in step (1) are blocked, and the blood inlet and outlet are connected to the peristaltic pump tubing. A certain mass of 1,3,5-trimethyl-2,4,6-tris[3,5-di(4-aminophenyl)phenyl]benzene is weighed and dissolved in ethanol to prepare a 1.0 mol / L mixed solution. The prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 8 hours at room temperature. Then the dialyzer is removed and dried in a vacuum drying oven at 80℃ for 4 hours to obtain a hemodialyzer with a certain amount of 1,3,5-trimethyl-2,4,6-tris[3,5-di(4-aminophenyl)phenyl]benzene deposited on the inner surface of the membrane.

[0044] Step (3) Preparation of modified coating: The dialysate inlet and outlet of the hemodialyzer from step (2) are blocked again, and the blood inlet and outlet are connected to the peristaltic pump pipeline. A certain mass of 2,5-disulfonic acid terephthalaldehyde is weighed and dissolved in pure water to prepare a 1.5 mol / L mixed solution. Under the condition of 80℃, the prepared mixed solution is circulated on the inner surface of the dialyzer membrane for 5 hours to react with the 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialyzer is removed and dried and sterilized to obtain the modified low-flux hemodialyzer.

[0045] Comparative Example 1 The difference from Example 1 is that the manufacturing processes in steps (2) and (3) are different: Step (2) Weigh a certain mass of 1,3,5-tris(4-aminophenyl)benzene and dissolve it in ethanol to prepare a 0.1 mol / L mixed solution. Soak the polyethersulfone hollow fiber membrane in the prepared mixed solution for 8 hours at room temperature, and then take it out and dry it in a vacuum drying oven at 80℃ for 4 hours to obtain a hollow fiber hemodialysis membrane with a certain amount of 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane.

[0046] Step (3) is the preparation of sulfonate aldehyde modified coating: a certain mass of 2,5-disulfonic acid terephthalaldehyde is dissolved in pure water to prepare a 0.15 mol / L mixed solution. Under the condition of 80℃, the hollow fiber hemodialysis membrane obtained in step 2 is immersed in the mixed solution for 5 hours and reacts with the 1,3,5-tris(4-aminophenyl)benzene deposited on the inner surface of the membrane in step (2) to obtain the target modified coating. Then the dialysis membrane is taken out and dried and sterilized to obtain the modified low-flux hemodialysis membrane.

[0047] Example 7 Performance Test The average pore size of the dialysis membrane base membrane and the modified coating two-dimensional network structure prepared in Examples 1-6 and Comparative Example 1 was determined by the bubble point method.

[0048] The results are shown in Table 1. Table 1. Pore size of dialysis membrane base and average pore size of modified coating in Examples 1-6 and Comparative Example 1.

[0049] The urea and creatinine clearance rates of the dialysis membranes prepared in Examples 1-6 and Comparative Example 1 were evaluated using a method of preparing a simulated solution. The albumin and β2-microglobulin screening coefficients, ultrafiltration coefficients, and leukocyte residues were tested using bovine plasma solution.

[0050] The results are shown in Table 2.

[0051] Table 2. Performance evaluation results of dialysis membranes in Examples 1-6 and Comparative Example 1.

[0052] The above results show that the low-flux hemodialysis membrane prepared by the method of the present invention has an albumin sieving coefficient of less than 0.01, while significantly improving the toxin removal efficiency. Compared with the traditional low-flux dialysis membrane, the removal efficiency of medium-molecular-weight toxins such as β2-microglobulin is also improved.

[0053] Unless otherwise stated, all technical terms and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. However, in case of conflict, the specification containing the definitions shall prevail. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to depart from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A surface-modified low-flux hemodialysis membrane, characterized in that, The dialysis membrane includes a base membrane and a modified coating located on the inner surface of the base membrane; The base membrane is a polyethersulfone hollow fiber membrane; the modified coating is a two-dimensional network structure formed by the polymerization reaction of aminobenzene substances and aldehyde substances containing sulfonic acid groups, the average pore size of the structure is 1.5 to 1.8 nm, and the two-dimensional network structure is rich in sulfonic acid groups; the albumin sieving coefficient of the dialysis membrane is less than 0.

01.

2. The surface-modified low-flux hemodialysis membrane according to claim 1, characterized in that, The aminobenzene compounds are selected from one or more of 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 1,3,5-tris(N-(p-methylphenyl)-N-(1-naphthyl)amino)benzene, 1,3,5-tris(N-(p-tert-butylphenyl)-N-(4-biphenyl)amino)benzene, 1,3,5-triaminobenzene, and 1,3,5-trimethyl-2,4,6-tris[3,5-di(4-aminophenyl)phenyl]benzene.

3. The surface-modified low-flux hemodialysis membrane according to claim 1, characterized in that, The sulfonic acid-containing aldehydes are selected from one or more of 2,5-disulfonic terephthalaldehyde, 4,4'-disulfonic biphenyl dicarboxaldehyde, 2-sulfonic-1,3-propanedialdehyde, and 1,2-bis(sulfonic acid methoxy)glyoxal.

4. The surface-modified low-flux hemodialysis membrane according to claim 1, characterized in that, The spinning solution of the base film contains the following components by mass fraction: Polyethersulfone resin: 14%–18%; Pore-forming agent: 1.5%–4.0%; Organic solvent A: 75%–80%; RO water: 1%~3%; The core fluid of the base membrane contains the following components by mass fraction: Organic solvent A: 40%–50%; RO water: 50% ~ 60%.

5. The surface-modified low-flux hemodialysis membrane according to claim 4, characterized in that, The organic solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

6. The surface-modified low-flux hemodialysis membrane according to claim 4, characterized in that, The pore-forming agent is one or more of polyvinylpyrrolidone and polyethylene glycol.

7. A method for preparing a surface-modified low-flux hemodialysis membrane as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Preparation of polyethersulfone hollow fiber membrane: Polyethersulfone resin, pore-forming agent, organic solvent A and RO water are mixed and stirred and degassed to obtain spinning solution; organic solvent A and RO water are mixed to obtain core solution, and spinning is carried out by phase inversion method. After washing and drying, polyethersulfone hollow fiber membrane with an average pore size of 2.8 to 3.2 nm on the inner surface is obtained. (2) Aminobenzene deposition: Circulate organic solvent B containing 0.1-1.0 mol / L aminobenzene substances on the inner surface of the polyethersulfone hollow fiber membrane described in step (1) for 6-10 h, and vacuum dry at 75-85 °C to constant weight; (3) Sulfonic acid aldehyde modification: The aqueous solution of aldehyde containing 0.15-1.5 mol / L sulfonic acid groups is circulated at 75-85°C on the inner surface of the polyethersulfone hollow fiber membrane after step (2) for 4-6 hours, and then vacuum dried at 75-85°C to constant weight.

8. The method according to claim 7, characterized in that, The stirring in step (1) is carried out at 70-90°C for 5-10 hours; the degassing is carried out under vacuum for 8-12 hours.

9. The method according to claim 7, characterized in that, The organic solvent B mentioned in step (2) is one or more of methanol, ethanol, and acetonitrile.

10. A hemodialysis device, characterized in that, It is prepared using the surface-modified low-flux hemodialysis membrane as described in any one of claims 1-6.

Citation Information

Patent Citations

  • Dialysis membrane for hemodialysis

    CN107930416A

  • A sulfonated citric acid chitosan-modified polysulfone hemodialysis membrane and its preparation method

    CN110756066B

  • Polyether sulfone hemodialysis membrane with heparin-like modified coating as well as preparation method and application of polyether sulfone hemodialysis membrane

    CN113559720A